1974
DOI: 10.1073/pnas.71.11.4472
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-Like Contractile Proteins and Tubulin in Synaptosomes

Abstract: Material in major bands with molecular weights corresponding to those of actin, brain tropomyosin, and myosin is present in purified rat synaptosomes dissolved in sodium dodecyl sulfate and subjected to electrophoresis on dodecyl sulfate-acrylamide gels. A band corresponding to tubulin appears to be the major constituent of synaptosomes, confirming the work of Feit and his coworkers. We have demonstrated by peptide mapping that the proteins in these bands have strong chemical similarities to actin, brain tropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
52
1

Year Published

1976
1976
1994
1994

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(57 citation statements)
references
References 35 publications
4
52
1
Order By: Relevance
“…As two independent methods of disrupting pig lymphocytes (see Materials and methods) gave rise to plasma membrane with similar actin contents, it appears unlikely that the association results from a particular method of cell rupture. In a similar study of synaptosomal membrane, Blitz and Fine [22] approached the problem of non-specific association by adding radiolabelled actin to the cell homogenate. They found that the purified membrane possessed essentially no radioactivity and concluded that the membraneassociated actin was 'intrinsic to the synaptosomes'.…”
Section: Discussionmentioning
confidence: 99%
“…As two independent methods of disrupting pig lymphocytes (see Materials and methods) gave rise to plasma membrane with similar actin contents, it appears unlikely that the association results from a particular method of cell rupture. In a similar study of synaptosomal membrane, Blitz and Fine [22] approached the problem of non-specific association by adding radiolabelled actin to the cell homogenate. They found that the purified membrane possessed essentially no radioactivity and concluded that the membraneassociated actin was 'intrinsic to the synaptosomes'.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there is increasing evidence for a direct association of tubulin (the major subunit component of microtubules) with membranes. For example, there is specific colchicine binding to isolated membrane fractions from brain (6, 10); and tubulin has been identified in synaptic vesicles by polyacrylamide gel electrophoresis (7, 11,19), by reaction with specific antibodies (33), and recently by analysis on two-dimensional electropheretograms and by tryptic peptide mapping (17). Stephens' (30) analyses of membranes of the scallop have also supported the existence of membrane-bound tubulin: it was clearly shown that tubulin is associated with ciliary but not flageUar membranes.…”
Section: Abstract Tubulin Membrane Disulfides Phospholipid Microtubumentioning
confidence: 99%
“…The similarity between Ca2l-stimulated actomyosin interactions and neurotransmitter release mechanisms has prompted many investigators to suggest that actin and myosin may be directly involved in the release of some neurotransmitters (2)(3)(4)(5)(6)(7)(8). Contractile processes in smooth muscle and nonmuscle cells are regulated by phosphorylation of the light chain of myosin by a Ca2+-calmodulin-dependent kinase (for review, see refs.…”
mentioning
confidence: 99%
“…Synaptosomes contain both actin and myosin (3,4) as well as a Ca2+-stimulated myosin-like ATPase activity, which is associated with synaptic vesicles (3). Actin has been identified in highly purified synaptic vesicle preparations (12) and is also present, mainly as unpolymerized Gactin, within neuronal cytoplasm (13).…”
mentioning
confidence: 99%